Peralihan Kredit Kendaraan Bermotor Secara Sepihak Tanpa Persetujuan - Huberth Adam Mainake; Sarah Selfina Kuahaty; Ronald Fadly Sopamena (Faculty of Law Universitas Pattimura, 2023)
ABSTRACT: Limited sources of funds that are able to overcome the installment needs of lower income groups are the driving reason for the development of Consumer Finance Companies. The aim of the research is to discuss and analyze the legal consequences of transferring credit without creditor approval and resolving disputes over transferred credit objects. Research method: normative juridical, using a statutory approach, with the hope of answering the problems faced. Legal Material Collection Procedures. This is done by means of literature study. The management of legal materials used uses qualitative methods. Research results in the mechanism for resolving consumer complaints through 2 (two) stages, namely resolving complaints carried out by financial services institutions (internal dispute resolution) and resolving disputes through judicial institutions or institutions outside the judiciary (external dispute resolution). The legal consequences for consumers (debtors) of the act of transferring by buying and selling motorbikes without the approval of the financing company (creditor) are categorized as having committed an act of violating Law Number 42 of 1999 concerning Fiduciary Guarantees so that the financing company has the right to carry out actions to execute fiduciary guarantees by means of motorbike withdrawal.